A clinical study of new cases of Hansen’s disease at a tertiary health care centre in post elimination era - Thimmappa, Raghu Mudigere; Deshpande, Shreya S.; Maheshwarappa, Yogendra; Ramesh, Rakesh Yelahanka (International Journal of Research in Dermatology, 2021)
Background: Leprosy, in 2016, globally a total of 214,783 new cases were reported over half of them were from India (135,485) alone. However, 16 other countries with pockets of high endemicity were reported. On the other hand, actual numbers of people affected by the disease is likely to be far higher than statistics show as there still prevails lack of awareness about the disease, lack of skills of general health staff in leprosy diagnosis, inadequate active case findings, lack of inclusion of cases from private sector and presence of high stigma in the community. Aims and objectives were to study the number of increasing new cases of Hansen’s disease in post elimination era. Methods: A prospective observational study of number of new cases of leprosy presented at a department of DVL, BMCH, Chitradurga, Karnataka, from 2017 April-2018 September. A total of 91 cases were detected. Results: Series of 91 cases were detected, and based on WHO classification were classified as multibacillary (MB)-72 cases and paucibacillary (PB)-19 cases. The maximum number of cases were detected between 20-29 years of age. The male to female ratio was 1.2:1. 46 (50.54%) cases were diagnosed to have borderline tuberculoid (BT). Patients mainly belonged to low socioeconomic status (89.1%). Deformities were seen in 21 (23.07%)) cases. 7 patients presented with type-I reaction and 13 patients with type-II reactions. Conclusions: Even with MB-MDT and monitoring, some high endemic pockets of leprosy may continue to persists in India. Every year new cases are increasing and causing morbidity from neglected cases. We should not be complacent at this stage because it may become a serious health problem again.